Application D-Optimal method on the optimization of green tea (Camellia sinensis L.) formulation - Andina, Ni Kadek Devi Pradnya; Darmawan, Fiki Dwi; Dewi, Ni Putu Intan Satya; Naripradnya, Putu Saradevi; Wijaya, Hendra; Parta, I Putu Rizki Karisma; Sutri, Wiratama Kadek; Angelina, Ariyanthini Elisabeth; Setyawan, Eka Indra (Universitas Muhammadiyah Magelang, 2021)
Green tea leaves contain many polyphenols and antioxidants that can reduce cell damage and prevent premature ageing. Green tea extract is made in gel preparation to make it easier to use and increase convenience. HPMC base with propylene glycol additives can increase drug release and penetration into the skin. This study aims to optimize HPMC and propylene glycol levels in green tea extract gel formulations using the D-optimal method and calculate the total release of polyphenols using the Franz diffusion cell method. The extract is produced by infundation. The gel preparation was formulated by varying HPMC and propylene glycol levels in the manufacturing process. Each gel was evaluated for its physical properties, namely viscosity test, pH test, and dispersion test. The physical properties data obtained were then analyzed using Design-Expert software in the mixture design program to get the optimum formula. The optimum procedure brought was HPMC with a concentration of 6% and propylene glycol with a concentration of 17%, resulting in the best correlation between viscosity, dispersion, and pH, with a desirability value of 0.921. In the green tea gel preparation, the resulting concentration was 8.00 GAE/g sample, and the gel content was released at 360 min. was 3.30 GAE/g sample. Keywords: D-Optional mixture design; green tea; HPMC; polyphenols; pharmacy care